2019
DOI: 10.1101/696476
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How sensitive is functional connectivity to electrode resampling on intracranial EEG? Implications for personalized network models in drug-resistant epilepsy

Abstract: Focal epilepsy is a clinical condition arising from disordered brain networks. Network models hold promise to map these networks, localize seizure generators, and inform targeted interventions to control seizures. However, incomplete sampling of epileptic brain due to sparse placement of intracranial electrodes may profoundly affect model results. In this study, we evaluate the robustness of several published network measures applied to intracranial electrode recordings and propose an algorithm, using network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…This could be due to an intrinsic difference in PZ connectivity between surgical responders and non-responders, a difference in SEEG implantation strategy between the patient groups that affects network observations, or a difference in ictal interpretation that affects node designation. 115117 With this observation as motivation, we developed SVM models to classify SOZs, PZs, and non-involved regions. The models were able to classify SOZs with very high accuracy (range of 91.4-92.5% accuracy) but differed in ability to differentiate PZs from non-involved regions (range of 81.6-93.0% accuracy).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to an intrinsic difference in PZ connectivity between surgical responders and non-responders, a difference in SEEG implantation strategy between the patient groups that affects network observations, or a difference in ictal interpretation that affects node designation. 115117 With this observation as motivation, we developed SVM models to classify SOZs, PZs, and non-involved regions. The models were able to classify SOZs with very high accuracy (range of 91.4-92.5% accuracy) but differed in ability to differentiate PZs from non-involved regions (range of 81.6-93.0% accuracy).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that such subnetworks do not necessarily have the same properties as the whole-brain network. Recent analyses demonstrated that even leaving out one node from iEEG functional networks can dramatically change their network properties (Conrad et al, 2019). The implication is that the property of the epileptogenic tissue/network may change depending on the subnetwork sampled, which may explain some conflicting results in the literature (Zijlmans et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…between outcome groups Spatially undersampling networks can directly lead to changes in the estimated network properties (Conrad et al, 2019), and thus we investigated the impact of spatial sampling on our ability to distinguish outcome groups. Fig.…”
Section: Increased Coverage Of Removed and Spared Tissue Improves Dis...mentioning
confidence: 99%